Antimicrobial study of the leaves extracts of atocarpus lanceifolius - Mohamed Safri, Fatim Nasuha; Bakhtiar, M. Taher; Darnis, Deny Susanti (2014)
Infectious diseases constitute an arising number of annual deaths recorded worldwide. The world is currently experiencing challenges of increased resistance development against available antimicrobial drugs. Therefore, the search for new antimicrobial drug is urgently needed to reduce the burden of disease globally. Traditional plants have been a prominent source in drug discovery. Artocarpuslanceifolius is used in this study as it is known to have many therapeutic values. Thus, the aim of this study is to screen for antimicrobial activity in the leaves extracts of A.lanceifolius against selected microorganisms. Extraction is done via Soxhlet apparatus with a series of solvents, n-Hexane, ethyl acetate and methanol in sequence of increasing polarity. Antimicrobial properties are evaluated using disc diffusion and broth microdilutionmethod. The obtained results showed that only methanol and ethyl acetate extracts exhibit antimicrobial properties whereas n-Hexane possessed no antimicrobial properties. Among the tested microorganisms, only Gram-positive bacteria (Bacillus cereus and Staphylococcus aureus) were found to be susceptible towards methanol extract (Inhibition zone: 11.33 - 12.33 mm; MIC value: 50 mg/ml; MBC value: 100 mg/ml) and ethyl acetate extract (Inhibition zone: 7.67 – 11.67 mm; MIC value: 50 and 100 mg/ml for B. cereus and S. aureus, respectively; MBC value: 100 mg/ml). Meanwhile, Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and fungi (Candidaalbicansand Aspergillus spp.) were found to be not sensitive towards all extracts.